Malka - Pressler, Mirjam; Murdoch, Brian (New York : Philomel Books, 2003)
In the winter of 1943, a Polish physician and her older daughter make a dangerous and arduous trek to Hungary while seven-year-old Malka, who they were forced to leave behind when she became ill, fends for herself in a ghetto.
Keywords: Jews -- Juvenile fiction; Holocaust, Jewish (1939-1945) -- Juvenile fiction; Jews -- Fiction; Holocaust, Jewish (1939-1945) -- Fiction; Survival -- Fiction; Mothers and daughters -- Fiction